Towards Lunar In-Situ Resource Utilization Based Subtractive Manufacturing - André Seidel; Uwe Teicher; Steffen Ihlenfeldt; Konstantin Sauer; Florian Morczinek; Martin Dix; Rick Niebergall; Bernhard Durschang; Stefan Linke (Applied Sciences, 2023)
In recent years, space agencies, such as the National Aeronautics and Space Administration (NASA) and European Space Agency (ESA), have expanded their research activities in the field of manufacturing in space. These measures serve to reduce limitations and costs through fairing size, launch mass capabilities or logistic missions. The objective, in turn, is to develop technologies and processes that enable on-demand manufacturing for long-term space missions and on other celestial bodies. Within these research activities, in-situ resource utilization (ISRU) and recycling are major topics to exploit local resources and save transport capacity and, therefore, costs. On the other hand, it is important to carefully consider which items can be brought and which must be manufactured on the Moon. Consequently, on-demand needs in future space missions are considered regarding frequency, raw material and required manufacturing processes according to investigations by ESA and NASA. In conclusion, manufacturing in space state-of-the-art shows a strong focus on additive processes, primarily considering semicrystalline or amorphous plastics. The subtractive processing of metallic or ceramic materials, in turn, currently represents a research gap. Consequently, an approach for in-situ resource utilization-based subtractive manufacturing in space is presented to supplement the existing processes. The latter uses a high-pressure jet of water, with regolith simulate as abrasive in suspension, being directed at the workpiece, which is moved to separate metal and glass. Proof-of-concept results are presented, including suitable process windows, achieved cutting geometries, as well as the effects of parameter variations on the system technology and consumables used. The focus of the investigations supplements the general requirements for the design of machine tools for space applications with inertial process-specific boundary conditions as a step towards higher technology maturity.